2016
DOI: 10.1016/j.ajic.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Airborne spread of infectious agents in the indoor environment

Abstract: Key Words:Respiratory droplet indoor air coughing droplet dispersion infection control environmental ventilation Background: Since the 2003 severe acute respiratory syndrome epidemic, scientific exploration of infection control is no longer restricted to microbiologists or medical scientists. Many studies have reported on the release, transport, and exposure of expiratory droplets because of respiratory activities. This review focuses on the airborne spread of infectious agents from mucus to mucus in the indoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
411
0
24

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 435 publications
(436 citation statements)
references
References 80 publications
1
411
0
24
Order By: Relevance
“…For example, Lindsley et al (27) measured the content of influenza virus in aerosol particles from human coughs, reporting that 35% of the influenza RNA detected was contained in particles >4 μm in aerodynamic diameter, whereas 23% were contained in particles of 1-4 μm diameter and 42% were in particles <1 μm in diameter, indicating that the majority of the viral RNA from human coughs was within the respirable size range. Also, aerosols generated by coughing patients infected with Mycobacterium tuberculosis were between the range of 0.65-4.7 μm in diameter (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lindsley et al (27) measured the content of influenza virus in aerosol particles from human coughs, reporting that 35% of the influenza RNA detected was contained in particles >4 μm in aerodynamic diameter, whereas 23% were contained in particles of 1-4 μm diameter and 42% were in particles <1 μm in diameter, indicating that the majority of the viral RNA from human coughs was within the respirable size range. Also, aerosols generated by coughing patients infected with Mycobacterium tuberculosis were between the range of 0.65-4.7 μm in diameter (29).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum or minimum values of variables generally represent the extreme weather conditions that help the virus development and transmission. For example, low wind velocity and high atmospheric pressure can increase the virus concentration in a certain room by hindering the airflow (Morawska, 2006;Wei and Li, 2016) and low sunshine duration will do less harm to the virus (Walker and Ko, 2007), as mentioned before. Furthermore, immune status and behavior pattern of individual may change in extreme weather conditions.…”
Section: Discussionmentioning
confidence: 87%
“…Whereas another research showed no effect of atmospheric pressure on HFMD . Considering that the occurrence of mumps is clustered and half of the mumps patients are students, the high atmospheric pressure and low wind velocity may increase the virus concentration in a certain classroom by hindering the airflow, particularly in winter, and then increase the incidence of mumps (Morawska, 2006;Wei and Li, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to these pathogen-containing droplets can occur via both short- (within 1–2 m of the source patient) and long- (beyond about 2 m in the indoor environment) range routes. The former is known as direct spray infection [2], in which relatively large (≥ 5 μm in diameter) droplets or droplet nuclei can be directly deposited on the nasal or oral mucosa of the new host. Short-range airborne exposure via smaller droplets or droplet nuclei is also important in close proximity infection [3].…”
Section: Introductionmentioning
confidence: 99%